Age of menarche in girls with sight organ diseases - Umławska, Wioletta (Polskie Towarzystwo Antropologiczne, 2000)
The paper attempts to clarify the reasons for sooner pubescence of girls with sight defects than that of their normally seeing peers. The age of menarche was considered depending on the degree of the sight impairment and the disease etiology as well as some selected factors of the socio-economic environment in the examined girls' families
Keywords: Sight impairment girls; Menarche; Pubescence